2017
DOI: 10.1016/j.schres.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of psychotropic drug treatment on sterol metabolism

Abstract: Cholesterol metabolism is vital for brain function. Previous work in cultured cells has shown that a number of psychotropic drugs inhibit the activity of 7-dehydrocholesterol reductase (DHCR7), an enzyme that catalyzes the final steps in cholesterol biosynthesis. This leads to the accumulation of 7-dehydrocholesterol (7DHC), a molecule that gives rise to oxysterols, vitamin D, and atypical neurosteroids. We examined levels of cholesterol and the cholesterol precursors desmosterol, lanosterol, 7DHC and its isom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 68 publications
3
47
0
Order By: Relevance
“…Several psychotropic medications have been shown to alter 7-DHC levels and metabolism. Most relevant to our findings, Korade et al, recently reported that the use of aripiprazole, haloperidol and trazodone in psychiatric patients and controls is correlated with increased 7-DHC levels in plasma [ 45 ]. Aripiprazole is a second generation antipsychotic that is sometimes used as an augmentation agent in depression resistant to first line therapies.…”
Section: Discussionsupporting
confidence: 77%
“…Several psychotropic medications have been shown to alter 7-DHC levels and metabolism. Most relevant to our findings, Korade et al, recently reported that the use of aripiprazole, haloperidol and trazodone in psychiatric patients and controls is correlated with increased 7-DHC levels in plasma [ 45 ]. Aripiprazole is a second generation antipsychotic that is sometimes used as an augmentation agent in depression resistant to first line therapies.…”
Section: Discussionsupporting
confidence: 77%
“…Evidence has showed that aripiprazole could inhibit the activity of 7-dehydrocholesterol reductase, thus leading to the accumulation of 7dehydrocholesterol, while olanzapine and paliperidone could not. 16 As a result, the rising vitamin D in schizophrenic patients treated with aripiprazole may be ascribed to the elevated concentration of its precursor 7-dehydrocholesterol (as shown in Figure 4). Aripiprazole, an atypical antipsychotic drug, performed its beneficial functions to improve schizophrenic symptom via partial agonist activity at D 2 receptors to normalize both hyperdopaminergic and hypodopaminergic states.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence showed that aripiprazole could increase circulating 7-dehydrocholesterol concentrations. 16,17 As a precursor of vitamin D, it could be postulated that the increased 7-dehydrocholesterol might have a potential positive effect on vitamin concentrations. However, there was a paucity of systematic research demonstrating the effects of atypical antipsychotics on vitamins.…”
mentioning
confidence: 99%
“…Nine compounds in the library were very potent, increasing levels of 7-DHC with a Z score greater than 100. Of these nine drugs, haloperidol, aripiprazole, and domiphen had previously been reported to affect 7-DHC levels in cell culture studies and/or in vivo (30). Six of the compounds (nebivolol, rotigotine, iloperidone, ziprasidone, dyclonine, and penfluridol) had not been previously linked to elevated 7-DHC.…”
Section: Fda Drugs Elevate 7-dhc Levelsmentioning
confidence: 99%
“…Perturbing DHCR7 activity has been a known human health risk since the 1960s when the DHCR7 inhibitor, AY-9944, was demonstrated to be teratogenic in rodent models (17). Since that time, a number of other chemicals have been identified as DHCR7 inhibitors and, similarly, their use is cautioned and/or altogether discontinued during pregnancy (30). In addition to increased risk of birth defects and perturbed fetal development, there is also the potential for DHCR7 inhibitors to pose increased health risks for adult patients as well.…”
Section: The Potential Risks Of Elevated Levels Of 7-dhcmentioning
confidence: 99%